O processo de formação de mediadores no Museu de Ciências e Tecnologia da PUCRS : entre saberes e fazeres, o ser da mediação - Giglio, Roberta (2016)
This article aimed at understanding the process of training/capacity-building of mediators at the Science and Technology Museum of the Pontifical Catholic University of Rio Grande do Sul (MCT-PUCRS). Grounded in a Case Study-type of qualitative approach, semi-structured interviews were carried out using the Focus Group technique to gather information related to the role and actions of these mediators at the Museum, as well as to their capacity-building process. The data collected from the semi-structured interviews were compared between the groups in order to some kind of consensus to be reached about the role of mediators at the MCT-PUCRS, so that it could be possible to understand how the training of these professionals happens. Based on the Discursive Textual Analysis methodology (MORAES; GALIAZZI, 2011), three categories were established. These categories were defined through the analysis of the questionnaires completed by the 20 mediators who participated in the research, as well as the analysis of the semi-structured interviews which were conducted with the focus groups, whose members were mediators, other employees and the managing team of the MCT-PUCRS. This whole process of construction and emergence of the categories resulted in a series of meaningful information and data about the reality of mediation at the MCT-PUCRS, and such facts enabled a deeper understanding of the process of capacity-building of mediators (an indispensable element of their training) and of how this is connected to the formation of a “mediating subject”. Additionally, by analyzing the results it was also possible to clearly see mediators who are imbricated in a series of interpersonal relations. Thus, the conclusion was that the training of a mediator occurs not only through capacity-building processes based on specific contents related to the interactive experiments of the Museum, but also by means of the life experience of these human beings, who deal with and relate to other individuals. It can be seen that the training of mediators involves aspects of subjective constitution, for the process of constitution of the “mediating being” does not happen only when these people become aware of their roles and responsibilities in the exhibition area of the Museum, but in the course of their human actions – among which the educational ones, for example, are a highlight – and also during their daily lives and exchanges of experiences with their co-workers and the general public.